El nivel de educación y el ingreso de los habitantes de la Ciudad de Riobamba período 2018 - Unach (2019)
The present study studies the level of education and income of the inhabitants of the city of Riobamba during the period 2018. Therefore, a survey was applied to the economically active population of the city of Riobamba, in which indicators such as: gender, marital status, level of education, sector in which he works, income, etc. The structure that has the present work is composed of four chapters, in the first reference is made to the approach of the problem, the formulation of the problem and the objectives. The second chapter refers to the State of the Art, in which the antecedents and the theoretical foundation of the two variables are raised: level of education and income. In the third chapter, the methodological framework of the research process is established, in which the hypothetical deductive method and the analytical method were applied, while at the same time containing the sample used for the application of surveys. The fourth chapter encompasses the results achieved through tabulation of data, to finally apply the econometric model using the Mincer equation where it was established that the level of education and experience affect 52% of the income of the economically active population of the city of Riobamba; Finally, the conclusions and recommendations of the research work were established.